Pengaruh Kebijakan Dividen, Leverage, dan Volume Perdagangan terhadap Volatilitas Harga Saham dengan Ukuran Perusahaan sebagai Variabel Moderasi : Studi pada Perusahaan yang Terdaftar dalam Indeks LQ45 di BEI Periode 2020-2024 - Rizki Eka Ariyanti; Sri Hasnawati (Jurnal Multidisiplin Indonesia, 2026)
This study examines how company fundamentals and external market conditions affect stock price volatility, such as dividend policy, leverage, and trading volume, with an emphasis on the function of company size as a moderating variable in LQ45 companies between 2020 and 2024. Standard deviation is used to calculate stock price volatility using the Parkinson 1980 approach. The Dividend Payout Ratio (DPR) is used as an indicator of dividend policy, leverage is calculated using the Debt to Equity Ratio (DER), and trading volume is calculated using Trading Volume Activity (TVA). Meanwhile, the natural logarithm transformation of total assets serves as a proxy for calculating company size. Purposive sampling was used to select 24 samples that met the research requirements. Secondary data from company annual reports and information on stock trading activity were used. The techniques used were multiple linear regression analysis and Moderated Regression Analysis (MRA). The estimation tool used was EViews 12 software. Data analysis shows that leverage has a negative effect on volatility and trading volume has a positive effect. However, the existence of a dividend policy does not cause significant changes in stock price volatility. Similarly, the MRA test found that firm size moderates the impact of the leverage-volatility relationship by strengthening it. Meanwhile, the impact of trading volume and the relationship between dividend policy and stock price volatility remain unchanged even after firm size is taken into account.